Involvement of tumor necrosis factor-α in the pathogenesis of autoimmune orchitis in rats - Suescun, María Olga (2003)
We studied the testicular macrophages of rats with experimental autoimmune orchitis (EAO) and analyzed whether the tumor necrosis factor-α (TNFα) is involved in germ cell apoptosis and in Leydig cell steroidogenesis. The EAO was induced in adult male Sprague-Dawley rats by active immunization with testicular homogenate and adjuvants. In the experimental group, a severe orchitis was observed 80 days after the first immunization. ED1- and ED2-positive macrophages were quantified by immunohistochemistry. The TNFα concentration of conditioned media from testicular macrophages (TMCM) was determined by ELISA. The number of apoptotic TNF receptor 1 (TNFR1)-positive germ cells was identified by combining in situ end labeling of apoptotic DNA and immunohistochemical techniques. The effect of TNFα on Leydig cell testosterone production was determined by RIA. In rats with EAO, we observed a significant increase in the number of TNFα-positive testicular macrophages, the TNFα concentration in TMCM, and the number of TNFR1-positive germ cells. Sixty percent of TNFR1-positive germ cells were apoptotic. These results suggest that TNFα could be involved in the pathogenesis of EAO. Acting together with other local factors such as Fas-FasL, TNFα could trigger germ cell apoptosis. We also demonstrated that TNFα inhibited in vitro testosterone production in basal and hCG-stimulated Leydig cells from rats with orchitis.